Technological Fit and the Market for Managerial Talent - Bereskin, Fred; Byun, Seong K.; Oh, Jong-Min (Journal of Financial and Quantitative Analysis, 2023)
Abstract We show that the similarity of a firm’s technological expertise with that of other firms affects managerial labor market outcomes. Using each firm’s patent portfolio to estimate its technological expertise, we find that its similarity in technological expertise with other firms is strongly related to the benchmark group used for CEO compensation and job transitions. Furthermore, we show that a firm’s CEO pay is positively associated with the CEO compensation levels of technologically similar firms. Our results thus demonstrate the crucial role of technological similarity in determining the value of outside options and the boundaries of the managerial labor market.